2017
DOI: 10.18203/2320-6012.ijrms20172454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical profile of liver abscess patients

Abstract: Background: Liver comprises 48% of all the visceral abscesses. It is common in India with 2nd highest incidence due to poor sanitation, overcrowding and inadequate nutrition. Worldwide, approximately 40-50 million people are infected annually with amoebic abscesses. This study aims to observe the clinical and biochemical profile of liver abscess patients so that a prompt diagnosis can be made and early treatment can be given.Methods: The study was conducted over a period of 1 year on 50 patients of liver absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The commonest clinical presentation observed in the study by Dhanapal PV et al was abdominal pain which was found in 100% of cases which was followed by abdominal distension and fever in about half of the cases. 15 This is also similar to the observations made by Jain V et al, Kemparaj P et al, and Kebede A et al 9,12,14…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The commonest clinical presentation observed in the study by Dhanapal PV et al was abdominal pain which was found in 100% of cases which was followed by abdominal distension and fever in about half of the cases. 15 This is also similar to the observations made by Jain V et al, Kemparaj P et al, and Kebede A et al 9,12,14…”
Section: Discussionsupporting
confidence: 83%
“…12,13 Jain V et al observed Pleural effusion was seen in 12% (n=6) cases whereas ascites was observed in 6% cases. 14 In a study by Dhanapal PV et al most of the liver abscess cases were managed with interventions. 15 About 30% of cases were treated by single aspiration and 20% of cases by multiple aspirations.…”
Section: Discussionmentioning
confidence: 99%
“…In present study alcohol consumption was seen as a major risk factor as 55.0% patients of ALA were exposed to it. Jain V et al & Ghosh et al 2,5 had 58.4 % & 72% alcoholic patients in their study respectively. Alcohol suppresses function of Kupffer cells (specialized macrophage) in liver which has important role in clearing amoeba.…”
Section: Discussionmentioning
confidence: 71%